Driving Whistleblowing Intention in Public Sector Organizations: Evidence from Local Government Agencies in Yogyakarta - Nazaruddin, Ietje; Ramadhanty, Rahmi; Yani, Indah (Public Accounting and Sustainability, 2025)
Research aims: This study aims to examine the determinants of whistleblowing intentions in the public sector, focusing on organizational commitment, job satisfaction, perceptions of the seriousness of violations, and personal costs associated with whistleblowing. Design/Methodology/Approach: This study employed a quantitative survey method. Questionnaires were distributed to 171 civil servants at the Main Office of the Social Services (CSMO) Agency of the Special Region of Yogyakarta. The data were analyzed using multiple linear regression with the assistance of SPSS. Research findings: This study shows that whistleblowing intention is positively and significantly influenced by organizational commitment (OC), organization’s ethical values (OEV), job satisfaction (JS), and perceptions of the seriousness of violations (SOV). Conversely, perceptions of personal cost (PC) are not found to have a considerable impact. Theoretical contribution/Originality: This study advances whistleblowing research in the public sector by introducing ethical values, demonstrating that moral values, organizational commitment, and job satisfaction are more important than personal costs in shaping whistleblowing intentions. Practitioner/Policy implication: These findings provide a basis for policymakers to design reporting systems that encourage organizational commitment, strengthen ethical values, and create a work environment that supports the courage to report without fear of personal risk.